Water jet cavitation peening : establishment of standards for process intensity evaluation - Toh, Ying Zhang (2017)
In many industries, such as aerospace, surface enhancement is a vital process to improve the fatigue life of components. Research has shown that maintaining a good surface finish and having high compressive residual stress improves fatigue strength. Thus, many surface enhancement processes, such as shot peening and laser peening, are focused on inducing high residual stresses. However, while some processes such as shot peening can generate high residual stresses, they also create poor surface finishing. On the other hand, laser peening, while producing high stresses with smooth finishing, is an expensive process. Water cavitation shot peening has emerged as a new surface enhancement process that is cheaper than laser peening, while producing smooth surface finishing. It is also capable of inducing high compressive residual stresses comparable to both shot peening and laser peening. This report explores the establishment of standards for process intensity evaluation. For processes such as shot peening, Almen strip testing has been used to quantify the intensity of the process. This quantification of intensity would be used to estimate the magnitude of compressive residual stresses induced in a peening workpiece. However, Almen strips require peening of the workpiece to be stopped while conducting testing. The focus of this report is to evaluate the viability of using acoustic emission to measure intensity for water cavitation shot peening. This method could be used for in situ monitoring of cavitation peening through the evaluation of the magnitude of the acoustic emission. An acoustic monitoring prototype was set up in conjunction with a water cavitation peening prototype to monitor the acoustic emission during the peening process. Experiments were conducted to measure the relationship between the magnitude of acoustic emission and intensity, as well as to measure the relationship between the magnitude of acoustic emission and residual stress. To quantify the relationship with intensity, peening was conducted on Almen strips while the acoustic emission was measured. For residual stress, peening was conducted on a stainless-steel coupon. This report aims to establish the viability of acoustic emission testing and to measure the correlation between acoustic emission and intensity. This report also outlines future work to be conducted on acoustic emission monitoring to achieve more reliable and comprehensive results.